ТИПЫ КОСВЕННОЙ РЕЧИ В НЕМЕЦКОМ ЛИТЕРАТУРНОМ ЯЗЫКЕ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article discusses the types of indirect speech in the German literary language, as well as the ways in which the excerpt is connected to the main sentence.